KEMAMPUAN PRASARANA LINGKUNGAN TERHADAP BENCANA PADA KAWASAN PERMUKIMAN PADAT PENDUDUK DI KELURAHAN PELITA, KOTA SAMARINDA - findia findia (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2020)
Good environmental infrastructure is infrastructure that allows the environment to function properly. Gang Masjid on Jalan Lambung Mangkurat Samarinda, known as Kampung Fashion, is a densely populated residential area prone to flooding and fires. This is caused by inadequate environmental infrastructure conditions such as narrow roads with high traffic density, solid buildings, building conditions dominated by wooden walls, poor drainage systems and inadequate waste disposal facilities and minimal fire fighting facilities causing high risks flood and fire disaster. To reduce the high risk of disasters, community awareness about their environment needs to be increased. Training citizens to respond to disasters can minimize losses arising from disasters.